Polar bear science: characterizing relationship patterns and identifying opportunities. (2nd January 2018) - Egunyu, Felicitas; Clark, Douglas A.; Bradford, Lori
ABSTRACT: The polar bear science network is a relatively young knowledge domain that was originally dominated by natural scientists but has evolved to include social scientists. We used social network analysis (SNA) to examine the existing patterns of collaboration within the network, look for opportunities for collaboration between researchers, and describe the roles of natural and social scientists within the network. We analyzed articles published by polar bear scientists over a 40-year period (1973–2013) using SNA. The results show that the network has a low density, which indicates a sparely connected network. The network cannot be divided into factions according to disciplines, indicating cross-discipline collaboration. The network is also hierarchical and held together by 10 researchers – who, if removed, result in a fragmented network. We discuss the implications of the network structure for research and the opportunities it offers for collaboration amongst polar bear researchers.